503PActivity of afatinib in patients (pts) with NSCLC harboring uncommon EGFR mutations: Pooled analysis of three large phase IIIB trials. (24th November 2019) - Passaro, A; De Marinis, F; Tu, H; Laktionov, K K; Feng, J; Poltoratskiy, A; Zhao, J; Tan, E-H; Gottfried, M; Lee, V; Kowalski, D; Yang, C-T; et al.
Abstract: Background: In the registrational trials, afatinib (afa) was active against NSCLC tumors harboring common and uncommon EGFR mutations, including G719X, L861Q and S768I, 1 and is approved in this setting. Here, we assess 1 st -line afa in pts with uncommon EGFR mutations treated in a 'real-world' setting in the largest analysis of its kind to date. Methods: Retrospective pooled analysis of three 'real-world' studies: an expanded-access program in Korea (1200.193); an Asian phase IIIB trial (1200.66); a global phase IIIB trial (mainly Europe; 1200.55). Pts had EGFR mutation-positive (EGFRm+) NSCLC, were EGFR TKI-naïve, and received afa 40 mg/day. Dose reduction was permitted (minimum 20 mg/day). Endpoints included time to symptomatic progression (TTSP), investigator-assessed PFS and ORR. Results: Overall, 1108 pts were treated with afa: median age, 61 yrs; female, 58%; ECOG PS of 0/1/2, 26%/70%/4%; asymptomatic brain metastases, 19%; 1 st -line afatinib, 69%. 198 (18%) had tumors harboring at least one uncommon mutation (exon 20 insertions [Ins20]: n = 70; T790M: n = 20; G719X: n = 41; L861Q: n = 47; S768I: n = 20; other: n = 25. Of note, 35% of pts had Ins20 mutations, a heterogeneous group generally resistant to EGFR TKIs). Median TTSP, PFS and ORR were 8.3 mos (95% CI 7.2–11.0), 7.4 mos (95% CI 6.0–9.0) and 37% respectively. Median duration of response was 10.2 mos (95% CI 8.4–12.9). In those pts with uncommon mutations and brain metastases, median TTSP and PFS were 7.6 mos (95% CI 4.6–10.1) and 7.4 mos (95% CI 4.6–9.1). Clinical activity in pts with uncommon mutations was greatest against tumors harboring G719X, L861Q or S768I. Some pts with Ins20 or T790M mutations appeared to benefit from treatment. Survival data in specific mutation subgroups will be presented. Conclusions: In this 'real-world' analysis, nearly 20% of pts with EGFRm+ NSCLC harbored uncommon EGFR mutations. Afa was active in a broad range of these pts, including some with Ins20 mutations. 1. Yang, JC. et al. Lancet Oncol 2015;16:830–8. Clinical trial identification: NCT01931306; NCT01953913; NCT01853826. Editorial acknowledgement: Lynn Pritchard of GeoMed, an Ashfield company, part of UDG Healthcare plc. Legal entity responsible for the study: Boehringer Ingelheim. Funding: Boehringer Ingelheim. Disclosure: F. De Marinis: Honoraria (self): Roche; Honoraria (self): AstraZeneca; Advisory / Consultancy: Takeda; Research grant / Funding (institution): Boehringer Ingelheim. V. Lee: Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self): Eli Lilly; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Merck Sharp & Dohme. L. Clementi: Full / Part-time employment: Boehringer Ingelheim. W. Tang: Full / Part-time employment: Boehringer Ingelheim. D.C-L. Huang: Full / Part-time employment: Boehringer Ingelheim. A. Cseh: Full / Part-time employment: Boehringer Ingelheim. K. Park: Advisory / Consultancy: AMGEN; Advisory / Consultancy: Astellas; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): AstraZeneca; Advisory / Consultancy: BluePrint; Advisory / Consultancy: BMS; Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer Ingelheim; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy: Hanmi; Advisory / Consultancy: KHK; Advisory / Consultancy: Loxo; Advisory / Consultancy: Merch KGaA; Advisory / Consultancy, Research grant / Funding (self): MSD; Advisory / Consultancy: ONO; Advisory / Consultancy: Roche. C. Zhou: Honoraria (self): BI; Honoraria (self): Roche; Honoraria (self): Sanofi; Honoraria (self): Hengrui; Honoraria (self): Qilu; Honoraria (self): MSD. Y-L. Wu: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Honoraria (self): Roche; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim; Honoraria (self): Pfizer; Honoraria (self): Eli Lilly; Honoraria (self): MDS; Honoraria (self): BMS. All other authors have declared no conflicts of interest.